2015
DOI: 10.1002/aenm.201500677
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Nanocarbon‐Based Architectures for Flexible Supercapacitors

Abstract: Supercapacitors (SCs), also called electrochemical capacitors, often show high power density, excellent charge/discharge rates, and long cycle life. The recent development of flexible and wearable electronic devices requires that their power sources be sufficiently compact and flexible to match these electronic components. Therefore, flexible SCs have attracted much attention to power current advanced electronics that can be flexible and wearable. In the past several years, many different strategies have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 228 publications
(493 reference statements)
1
42
0
Order By: Relevance
“…The first step in constructing SAG is the large‐scale production of graphene and its derivatives with controlled structures and chemical properties . High‐quality graphene sheets can be prepared by various methods such as manual mechanical cleavage of graphite and chemical vapor deposition (CVD) .…”
Section: Fabrication Strategies and Characteristic Methods Of Sagmentioning
confidence: 99%
“…The first step in constructing SAG is the large‐scale production of graphene and its derivatives with controlled structures and chemical properties . High‐quality graphene sheets can be prepared by various methods such as manual mechanical cleavage of graphite and chemical vapor deposition (CVD) .…”
Section: Fabrication Strategies and Characteristic Methods Of Sagmentioning
confidence: 99%
“…Vast results have shown that these nanomaterials hold many prominent properties that are particularly adaptive for SCs devices. [126] …”
Section: Carbon Nanomaterials In Supercapacitorsmentioning
confidence: 99%
“…It can be categorized into electric double-layer capacitor (EDLC), pseudocapacitor, and newly evolving lithiumion capacitor [53]. With advantages on synergetic effects on electrochemical performance, CNT-polymer nanocomposites play significant roles on supercapacitors that integrate interfacial adsorption and redox reaction, hierarchical microstructure, conductivity, mechanical strength, and flexibility [54][55][56][57]. The following section focuses on current design and material synthesis of CNT-polymer nanocomposites in the pursuit of true performance matrices, that is, volumetric/areal performance.…”
Section: Carbon Nanotube-polymer Nanocomposites For Supercapacitorsmentioning
confidence: 99%
“…The unique characteristics of CNT facilitate its role in supercapacitor as electrode, conducting additive, template/scaffold for nanocomposite electrode, platform for flexible/stretchable device [54][55][56][57]. However, the shortcomings are worthy of noting.…”
Section: Current Challenge and Strategies For Cnt-based Electrode Matmentioning
confidence: 99%